Reverse colonization : science fiction, imperial fantasy, and alt-victimhood - Higgins, David M. (David Michael) (New American canon., 2021)
"Reverse colonization narratives are stories like H. G. Wells's War of the Worlds (where technologically superior Martians invade and colonize England) that ask Western audiences to imagine what it's like to be the colonized rather than the colonizers. In this book, David M. Higgins argues that although some reverse colonization stories are thoughtful and provocative (because they ask us to think critically about what empire feels like from the receiving end), reverse colonization fantasy has also led to the prevalence of a very dangerous kind of science fictional thinking in our current political culture. Everyone, now (including anti-feminists, white supremacists, and far-right reactionaries) likes to imagine themselves as the Rebel Alliance fighting against the Empire (or Neo trying to escape the Matrix, or Katniss Everdeen waging war against the Capitol). Reverse colonization fantasy, in other words, has a dangerous tendency to enable white men (and other subjects of privilege) to appropriate a sense of victimhood for their own social and political advantage"--